NFAT2 Regulates Generation of Innate-Like CD8+ T Lymphocytes and CD8+ T Lymphocytes Responses - Pachulec, Emilia; Neitzke-Montinelli, Vanessa; Viola, João P. B. (Frontiers in Immunology, 2016)
NFAT2 null mutant mice die in utero of cardiac failure, precluding analysis of the role of NFAT2 in lymphocyte responses. Only the NFAT2-/-/Rag-1-/- chimeric mice model gave insight into the role of NFAT2 transcription factor in T lymphocyte development, activation and differentiation. As reports are mainly focused on the role of NFAT2 in CD4+ T lymphocytes activation and differentiation, we decided to investigate NFAT2’s impact on CD8+ T lymphocytes responses. We report that NFAT2 is phosphorylated and inactive in the cytoplasm of naive CD8+ T cells, and upon TCR stimulation is dephosphorylated and translocated into the nucleus. To study the role of NFAT2 in CD8+ T responses we employed NFAT2fl/flCD4-Cre mice with NFAT2 deletion specifically in T cells. Interestingly, the absence of NFAT2 in T cells resulted in increased percentage of nonconventional innate-like CD8+ T cells. These cells were CD122+, rapid producer of IFN-γ and had characteristics of conventional memory CD8+ T cells. We also observed an expansion of PLZF+ expressing CD3+ thymocytes population in the absence of NFAT2 and increased IL-4 production. Furthermore, we found that CD8+ T lymphocytes deficient in NFAT2 had reduced activation, proliferation and IFN-γ and IL-2 production at suboptimal TCR strength. NFAT2 absence did not influence significantly differentiation of CD8+ T cells into cytotoxic effector cells, but reduced theirs IFN-γ production. This work documents NFAT2 as a negative regulator of innate-like CD8+ T cells development. NFAT2 is required for a complete CD8+ T cells responses at suboptimal TCR stimulation and regulates IFN-γ production by cytotoxic CD8+ T cells in vitro.